Pengaruh Celebrity Endorser Dan Word Of Mouth Terhadap Keputusan Pembelian Produk Scarlett Whitening Pada Mahasiswa UIN Sulthan Thaha Saifuddin Jambi - Jumianti Jumianti; Efni Anita; Nurrahma Sari Putri (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
The thesis with the title "The Influence of Celebrity Endorsers and Word of Mouth on the Decision to Purchase Scarlett Whitening Products among UIN Sulthan Thaha Saifuddin Jambi Students" was written by Jumianti with NIM 501190273, Sharia Economics Study Program, Sulthan Thaha Saifuddin Jambi State Islamic University 2023. This research aims to determine: (1) the influence of celebrity endorsers on purchasing decisions for Scarlett Whitening products, (2) the influence of word of mouth on purchasing decisions for Scarlett Whitening products, and (3) the influence of celebrity endorsers and word of mouth on purchasing decisions for Scarlett Whitening products.This research uses quantitative research methods by collecting data or survey methods. The sample in this research was 100 students at UIN Sulthan Thaha Saifuddin Jambi. The data collection technique uses a questionnaire whose validity and reliability have been tested. The data analysis technique used to answer the hypothesis is multiple regression. The results of this research show that: (1) Celebrity Endorser has no influence on purchasing decisions, as evidenced by the calculated t value of 0.191 with a significance value of 0.849 which is greater than 0.01. (2) word of mouth has a positive and significant effect on purchasing decisions, as evidenced by the calculated t value of 9.189 with a significance value of 0.000 which is smaller than 0.01. (3) celebrity endorsers and word of mouth simultaneously influence purchasing decisions, as evidenced by the calculated F value of 80.672 with a significance value of 0.000 which is smaller than 0.01. The adjusted R square value of 0.585 shows that the ability of the independent variable to influence the dependent variable is 58.5% and the remaining 41.5% is influenced by other variables outside this research